2011
DOI: 10.1111/j.1365-2958.2011.07674.x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a complex regulatory cascade involving the SirA/BarA and Csr global regulatory systems that controls expression of the Salmonella SPI‐1 and SPI‐2 virulence regulons through HilD

Abstract: Summary Salmonella pathogenicity islands 1 and 2 (SPI-1 and SPI-2) play key roles in the pathogenesis of Salmonella enterica. Previously, we showed that when Salmonella grows in LB medium HilD, encoded in SPI-1, first induces the expression of hilA, located in SPI-1, and subsequently of the ssrAB operon, located in SPI-2. These genes code for HilA and the SsrA/B two-component system, the positive regulators of the SPI-1 and SPI-2 regulons, respectively. In this study, we demonstrate that CsrA, a global regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
175
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(190 citation statements)
references
References 91 publications
(199 reference statements)
12
175
0
Order By: Relevance
“…UvrY protein was phosphorylated by incubation with 100 mM lithium potassium acetyl-phosphate (SigmaAldrich) for 60 min at room temperature in a buffer containing 50 mM HEPES, 100 mM NaCl, and 10 mM MgCl 2 as described previously (40).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…UvrY protein was phosphorylated by incubation with 100 mM lithium potassium acetyl-phosphate (SigmaAldrich) for 60 min at room temperature in a buffer containing 50 mM HEPES, 100 mM NaCl, and 10 mM MgCl 2 as described previously (40).…”
Section: Methodsmentioning
confidence: 99%
“…Fluctuations in the levels of these RNAs regulate CsrA activity in response to the environment. Transcription of both csrB and csrC (csrB/C) is activated by the BarA-UvrY two-component signal transduction system (TCS) in response to carboxylic acids such as formate and acetate (3,(36)(37)(38)(39)(40)(41). CsrA indirectly activates transcription of CsrB and CsrC through its effects on BarA-UvrY, creating a negative-feedback loop within the Csr circuitry (37,38,42).…”
mentioning
confidence: 99%
“…However, the regulation and function of the Salmonella T3SSs may be more complicated. SPI1 and SPI2, which contribute to inflammation, and the anaerobic respiration pathways that take advantage of inflammation are all regulated by CsrA, as detailed below (98,269).…”
Section: Salmonella Speciesmentioning
confidence: 99%
“…The effects of barA, sirA, csrB, and csrC on SPI1 are mediated through the binding of CsrA to the hilD transcript (269). BarA phosphorylates SirA (73,269), which then binds as a dimer to an 18-bp inverted repeat sequence between positions Ϫ190 and Ϫ173 of csrB and Ϫ168 and Ϫ151 of csrC relative to their transcription start sites (63).…”
Section: Salmonella Speciesmentioning
confidence: 99%
“…One such mechanism involves a small (61-aminoacid) protein, named CsrA, acting as a post-transcriptional regulator. Originally discovered as a repressor of glycogen biosynthesis in Escherichia coli (Romeo et al 1993), CsrA was subsequently found to regulate other growth phasedependent processes such as biofilm formation and quorum sensing in E. coli and Vibrio cholerae (Jackson et al 2002;Lenz et al 2005;Wang et al 2005;Yakhnin et al 2011) and host invasion in Salmonella (Altier et al 2000;Lawhon et al 2003;Martinez et al 2011). The CsrA structural homologs RsmA/RsmE perform similar functions in Pseudomonas and Erwinia species, where they participate in the regulation of secondary metabolism Cui et al 1995;Pessi et al 2001;Lapouge et al 2007).…”
mentioning
confidence: 99%